2021
DOI: 10.1080/00313831.2021.1897879
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Programming in Swedish School Mathematics: Investigating Elementary Mathematics Textbooks

Abstract: We characterize the recently included programming content in Swedish mathematics textbooks for elementary school. Especially, the connection between programming content and traditional mathematical content has been considered. The analytical tools used are based on the so-called 5E's, a theoretical framework of action, developed within the ScratchMath project, and Brennan and Resnick's (2012) terms computational concepts and practices. The result uncovers "follow a procedure" as the dominating action, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Second, key elements of how the scientific endeavor operates also play central roles in data science such as cycling through data for discoveries and reliance on reproducibility (Blei & Smyth, 2017). Some components of data science, as thus conceptualized, are already formally incorporated in the curriculum of elementary and secondary school systems via data visualizations (e.g., graph learning) (Aksoy & Bostan, 2021), descriptive and inferential statistics (e.g., distributional reasoning) (Biehler et al, 2018), data processing (e.g., in science inquiry) (Watson, 2017), and programming (Bråting & Kilhamn, 2021).…”
Section: Learning About Data In Elementary Mathematicsmentioning
confidence: 99%
“…Second, key elements of how the scientific endeavor operates also play central roles in data science such as cycling through data for discoveries and reliance on reproducibility (Blei & Smyth, 2017). Some components of data science, as thus conceptualized, are already formally incorporated in the curriculum of elementary and secondary school systems via data visualizations (e.g., graph learning) (Aksoy & Bostan, 2021), descriptive and inferential statistics (e.g., distributional reasoning) (Biehler et al, 2018), data processing (e.g., in science inquiry) (Watson, 2017), and programming (Bråting & Kilhamn, 2021).…”
Section: Learning About Data In Elementary Mathematicsmentioning
confidence: 99%
“…Instead of being a teacher, students work in minor groups with the teacher acting as a facilitator or supervisor. As students study to be extra autonomous in their method rather than depend solely on professors, the method has the ability to increase responsibility and motivation in the process of learning (Dirckinck-Holmfeld, 2002;Loyens et al, 2008;Bråting & Kilhamn, 2022). According to Prieto (2006), PWA encourages students to use real-world challenges as a springboard for learning and integrating new information.…”
Section: Related Workmentioning
confidence: 99%
“…Since programming is now a mandatory part of the curriculum, several mathematics textbooks include programming. However, analyses of these textbooks found that programming is often treated as tangential to mathematics and that there is a primary focus on introducing students to programming procedures rather than programming concepts (Bråting & Kilhamn, 2022). A recent study of mathematics teachers' teaching of these new subjects in the context of their specialisation (Kilhamn et al, 2021) showed that one third of the lessons that include programming did not connect it to mathematical content, and few explicit connections were made to algebra.…”
Section: Internalisationmentioning
confidence: 99%